Committed action in practice : a clinician's guide to assessing, planning & supporting change in your client - Moran, Daniel J. (Context Press mastering ACT series., 2018)
Designed for use by mental health professionals and graduate students, Committed Action in Practice clearly conceptualizes committed action--an integral aspect of acceptance and commitment therapy (ACT)--and offers a deeper investigation of the first of the six core processes of ACT. The book also provides comprehensive descriptions and insight into the conceptualization, integration, and application of committed action in therapy.--